Optimizing the Recruitment Process of Constitutional Judges to Enforce Independence and Legal Justice in Indonesia - Achmad Taufan Soedirjo; Faisal Santiago (International Journal Labs, 2023)
This research aims to analyze and propose optimizing the recruitment process for Constitutional Judges in Indonesia to uphold independence and legal justice. The research method used is the normative juridical method, which emphasizes the analysis of legal norms related to the recruitment process for Constitutional Judges. The discussion involves an in-depth review of relevant statutory articles, such as the 1945 Constitution of the Republic of Indonesia, the Constitutional Court Law, and other implementing regulations. In the discussion process, it was discovered that there was a need for increased transparency, public participation, and stricter selection criteria to ensure the integrity of Constitutional Judges. Certain articles, such as Article 24B of the 1945 Constitution, underline the importance of maintaining the independence of Constitutional Judges as guardians of the Constitution. The results of this discussion state that reforms in the recruitment process need to be carried out to ensure that the selected judges have high capacity and integrity. This research concludes that by optimizing the recruitment process for Constitutional Judges, the independence of the institution can be strengthened, as well as increasing public confidence in legal justice. It is hoped that increasing transparency and public participation can produce Constitutional Judges who can maintain justice and the sustainability of the Indonesian legal system.